Imaging of the Postsurgical Thoracic Aorta: A State-of-the-Art Review. Issue 1 (January 2017) - Latson, Larry A.; DeAnda, Abe; Ko, Jane P.
Abstract : Techniques for repair of the aorta currently include open and endovascular methods, hybrid approaches, minimally-invasive techniques, and aortic branch vessel reimplantation or bypass. Collaboration among radiologists and vascular and cardiothoracic surgeons is essential. An awareness of the various surgical techniques, expected postoperative appearance, and potential complications is essential for radiologists. This review will cover the postoperative appearance of the thoracic aorta with a focus on the ascending aorta. The value of three-dimensional image evaluation will also be emphasized.